Design of Preventive Maintenance System for A Product Design Lab using Reliability Centered Maintenance (RCM) Methodology - Marpaung, Bintang Rachel Aprilia; Manik, Yosef; Siboro, Benedikta Anna Haulian (Jurnal IPTEK, 2021)
The product design and innovation laboratory, which is still relatively new, does not yet have a maintenance model to anticipate damages that may occur in the future. The purpose of this research is to build preventive maintenance to anticipate unwanted events such as sudden damage and Standard Operational Procedure (SOP) for laboratory facilities. The method used is Reliability Centered Maintenance (RCM) using EasyFit 5.5 software, obtained a repair schedule with minimum downtime. The results of the Reliability Centered Maintenance (RCM) method obtained maintenance recommendations in the form of Condition Directed (CD) on 14 components that might damage the product design and innovation laboratory facilities, Finding Failure (FF) on 8 components that might damage the design laboratory facilities. products and innovations and Time Directed (TD) on 5 components that may cause damage to product design and innovation laboratory facilities, and also Based on the results of preventive maintenance built, there is a Standard Operational Procedure (SOP) which includes the use of laboratory facilities following work instructions for the use of equipment, use of facilities the laboratory follows the work instructions for use, all validation results must be stored in the form of records in the form